Implementation of Atraumatic Care Reduces Children’s Anxiety : A Cross Sectional Study - Khayati, Fitriana Noor; Sulistyowati, Arlina Dhian (Indonesian Journal of Global Health Research, 2024)
Hospitalization has an impact on children, one of which is anxiety. One effort that nurses can make to reduce anxiety in children is implementing atraumatic care. X hospital in Klaten as a maternal and child hospital has a large number of pediatric patients and guarantees care for children using the principles of atraumatic care. This study aims to determine the relationship between the application of atraumatic care and children's anxiety at X Hospital. This research design was a type of quantitative research with a cross-sectional approach. The population in this study was 122 people with a sample size of 45 people. The sampling technique used was non-probability sampling using accidental sampling. Data collection used a questionnaire. Data analysis used univariate and bivariate analysis using the Fisher Exact test with an error level of α=0.05. The characteristics of the respondents in this study are that the average age of the respondents is 108 months, 60% of the respondents are male, the average experience of children being hospitalized is 1.29 times, and the experience of children being sick is 0.69 times. Most of the implementation of atraumatic care at X Hospital was in a good category, namely 27 people (60%). All children's anxiety levels were normal (100%). There is no significant relationship between the application of atraumatic care and children's anxiety (p-value 0.662). There is no significant relationship between the application of atraumatic care and children's anxiety.